Cerebral Myelination in a Bronchopulmonary Dysplasia Murine Model - Wenwen Chen; Ran Wang; Chao Chen (MDPI AG, 2023)
Introduction: Bronchopulmonary dysplasia (BPD) is a devastating disease in preterm infants concurrent with neurodevelopmental disorders. Chronic hyperoxia exposure might also cause brain injury, but the evidence was insufficient. Methods: Neonatal C57BL/6J mice were exposed to hyperoxia from P0 to induce a BPD disease model. Lung histopathological morphology analyses were performed at P10, P15, and P20. Cerebral myelination was assessed using MBP (myelin basic protein, a major myelin protein), NfH (neurofilament heavy chain, a biomarker of neurofilament heavy chain), and GFAP (glial fibrillary acidic protein, a marker of astrocytes) as biomarkers by western blot and immunofluorescence. Results: Mice exposed to hyperoxia exhibited reduced and enlarged alveoli in lungs. During hyperoxia exposure, MBP declined at P10, but then increased to a comparable level to the air group at P15 and P20. Meanwhile, GFAP elevated significantly at P10, and the elevation sustained to P15 and P20. Conclusion: Neonatal hyperoxia exposure caused an arrest of lung development, as well as an obstacle of myelination process in white matter of the immature brain, with a decline of MBP in the generation period of myelin and persistent astrogliosis.